Syndetic structure of Dabaweñana subject and authority records - Merced, Briccio M., Jr (PLAI National Congress and General Assemby, 2016)
Aware of its role in promoting, protecting, and providing access to information on the history, rich culture and other vital information regarding the City, the Davao City Public Library and Information Center strives to develop its collection through aggressively collecting materials in print and non-print form. While continuous effort is being undertaken to acquire Dabaweñana materials, it is equally of paramount importance that management and organization of its collection be undertaken to achieve maximum utilization of recorded information. The paper aims to present the usefulness and importance of a syndetic structure for Davawenana subject and authority records for the benefit of both its local and foreign users. Authority files generate cross-references that promote used rather than the unused headings, direct users to related terms, enhance collocation, provide faster and accurate retrieval capability, and save much time to catalogers once the system becomes operational.